REVIEW: Emancipation and hegemony. Epistemological modulations V. Regional contributions to the debate - Cristina Ambrosini (Perspectivas Metodológicas​)
With this book, the Specialization and the Master's Degree in Scientific Research Methodology, two postgraduate courses of the Department of Humanities and Arts of the UNLa, inaugurate the editorial line of publication of digital books of the UNLa. This publication is part of the "open access" movement, that is, free access without the requirement of validation with a password or subscription or payment. In this sense, it responds to the policy of the Institutional Digital Repository "José María Rosa", created by Resolution CS 206/11, of giving greater visibility to academic productions, in Spanish, based in Latin American countries, since the digital repository allows search and retrieval in archives for both national and international use. In our country, the State is the main promoter of scientific research, through the financing of its activities and therefore public and free access to scientific-technological production contributes to substantiate in concrete actions one of the founding values of the UNLa: the democratization of knowledge. The open access policy for digital publications has a fruitful journey, in these two UNLa postgraduate courses, also with the Portal of Scientific Journals of the UNLa Arturo Peña Lillo.